Mitochondrial DNA-Mediated Inflammation in Acute Kidney Injury and Chronic Kidney Disease. (30th June 2021) - Jin, Lini; Yu, Binfeng; Armando, Ines; Han, Fei
Abstract : The integrity and function of mitochondria are essential for normal kidney physiology. Mitochondrial DNA (mtDNA) has been widely a concern in recent years because its abnormalities may result in disruption of aerobic respiration, cellular dysfunction, and even cell death. Particularly, aberrant mtDNA copy number (mtDNA-CN) is associated with the development of acute kidney injury and chronic kidney disease, and urinary mtDNA-CN shows the potential to be a promising indicator for clinical diagnosis and evaluation of kidney function. Several lines of evidence suggest that mtDNA may also trigger innate immunity, leading to kidney inflammation and fibrosis. In mechanism, mtDNA can be released into the cytoplasm under cell stress and recognized by multiple DNA-sensing mechanisms, including Toll-like receptor 9 (TLR9), cytosolic cGAS-stimulator of interferon genes (STING) signaling, and inflammasome activation, which then mediate downstream inflammatory cascades. In this review, we summarize the characteristics of these mtDNA-sensing pathways mediating inflammatory responses and their role in the pathogenesis of acute kidney injury, nondiabetic chronic kidney disease, and diabetic kidney disease. In addition, we highlight targeting of mtDNA-mediated inflammatory pathways as a novel therapeutic target for these kidney diseases.